M. Merleau-Ponty and the Effects of Silence in Literature. A Reflection on the Relationship between Philosophy and Artistic Language - Molina Ortiz, Gabriela (Resonancias. Revista de Filosofía, 2018)
This paper analyzes the merleau-pontian vision concerning the relationship between philosophy and literature expressed in what the French philosopher conceived as artistic language. The philosopher will proposes an alternative in the analysis of the silence that is manifested in the artistic language. We will inquire, therefore, on issues of art (painting) and literature observed from his posthumous work La prose du monde, which is a reflection that consider the importance of literary language, as well as existence, and as to what the philosopher conceives about language. From understanding the voices of silence as a living language, we will be able to see the link between literature and philosophy, which opens our study to a reflection of the possibility.